The effects of nanosized particles on microstructural evolution of an in-situ TiB2/6063Al composite produced by friction stir processing. (25th December 2015) - Chen, Z.; Li, J.; Borbely, A.; Ji, G.; Zhong, S.Y.; Wu, Y.; Wang, M.L.; Wang, H.W.
Abstract: The homogenous redistribution of nanosized TiB2 particles in a fine-grained in-situ AA6063/TiB2 composite has been achieved by friction stir processing (FSP). The effects of TiB2 particles on as-deformed structure in the nugget zone and its thermal stability after additional T6 heat treatment are quantitatively evaluated by using neutron diffraction, scanning electron microscopy associated with electron backscatter diffraction and synchrotron X-ray line profile analysis. The results are compared to those obtained from a FSPed AA6063 alloy and, show first that, average grain size of the FSPed AA6063/TiB2 composite is smaller than that of the FSPed AA6063 alloy, while grain size distribution is more uniform. Second, dislocation density estimated in the FSPed AA6063/TiB2 composite is higher than that in the FSPed AA6063 alloy. Third, a small number of grains are dynamically recrystallized in the FSPed AA6063/TiB2 composite compared to its alloy counterpart, which indicates that recrystallization and grain growth during FSP and T6 heat treatment are effectively inhibited by the presence of nanosized TiB2 particles. Graphical abstract: Highlights: Effects of TiB2 particles on microstructural evolution during FSP are quantitatively studied. Neutron diffraction is used to characterize texture of massive volume samples. Dislocation density is analyzed by synchrotron X-ray line profile analysis. Improved thermal stability of the UFG structure is due to homogeneous distribution of nanosized particles.